Kırsaldaki kadın kooperatiflerinde liderlik ve kurumsallaşma (Bursa örneği) - Şenlik, Betül (Bursa Teknik Üniversitesi, 2022)
Bu araştırmada ülke kalkınması için önemli bir rolü olan ve ayrıca kadın girişimciliğini geliştirmek için en uygun araçlardan birisi olarak nitelenen kadın kooperatiflerindeki liderlik tarzları ve liderlik tarzlarının kadın kooperatiflerinin kurumsallaşması üzerindeki etkileri incelenmiştir. Bu kapsamda kadın kooperatiflerindeki kadın kooperatif yöneticilerinin ve kooperatif ortaklarının görüşleri doğrultusunda kooperatiflerde görülen liderlik tarzları ve kurumsallaşma boyutları incelenecektir. Kurumsallaşma örgütlerin belirlenmiş amaçları doğrultusunda hedeflerine ulaşmak için bir değer ve standartlarla yönetilmesini gerektirmektedir. Kadın kooperatiflerinde kurumsallaşma alt boyutlarından olan şeffaflık, adaletle yönetim, resmileştirme profesyonellik ilkelerinin niteliksel durumları ve bu kooperatiflerde standartlaşma süreçleri incelenecektir. Türkiye de Ticaret Bakanlığı, 2021 verilerine göre ülkemizde aktif olarak 594 kadın kooperatifi bulunmaktadır. Bunların büyük çoğunluğu kadın girişimi üretim ve işletme kooperatifleridir. Bursa da ise kadın kooperatif sayısı 35'dir. Kırsal alanda faaliyet gösteren kadın kooperatif sayısının ise 25 olduğu ve kadın kooperatiflerinin yoğunluklu olarak kırsal alanda faaliyet yaptığı görülmüştür. Bu araştırmanın verileri, Bursa ilinde faaliyet gösteren 12 farklı kadın kooperatifinin başkanları, yönetim kurulu üyeleri ve ortaklarından oluşan 21 kadın ile derinlemesine görüşme yöntemiyle toplanmıştır. Nitel yöntemle yürütülen araştırma bulgularına göre görüşülen 21 kadın üyeden 19'u evli, 2 kişi ise bekardır. Bu kadınların 9'u 20-40 yaş aralığında, 5'i 41-50 yaş aralığında, 7'si ise 51 yaş ve üzeridir. Mülakat yapılan katılımcılardan 11 kişinin tecrübesi 5 yıldan az iken 10 kişinin 5 yılın üzerinde kooperatifçilik deneyimi vardır. Katılımcıların kooperatifçilik deneyimleri ile kendi kooperatiflerinde çalışma sürelerinin aynı olması, bulundukları kooperatifte devamlılık sağladıklarını göstermektedir. Yaş aralıklarına bakıldığında çocuklarını büyütmüş kadınların daha çok kooperatifin yönetim organlarında olmayı tercih ettiği söylenebilir. Kadın kooperatiflerinde görülen liderlik tarzı sırasıyla otokratik liderlik, dönüşümcü liderlik, serbest bırakıcı liderlik, demokratik liderlik ve etkileşimci liderlik olarak görülmüştür. Bu görüşmeler neticesinde kadın kooperatiflerinin kurumsallaşmalarında öne çıkan bulgulara bakıldığında, dönüşümcü liderlikte kurumsallaşma düzeyinin daha yüksek olduğu, ikinci sırayı otokratik liderliğin aldığı ve en düşük kurumsallaşmanın ise serbest bırakıcı liderlerin yönetiminde olduğu görülmüştür.

In this research, leadership styles in women's cooperatives, which have an important role in the development of the country and are also described as one of the most appropriate tools to develop women's entrepreneurship, and the effects of leadership styles on the institutionalization of women's cooperatives were examined. In this context, leadership styles and institutionalization dimensions in cooperatives will be examined in line with the views of women's cooperative managers and cooperative members in women's cooperatives. Institutionalization requires organizations to be managed with values and standards in order to achieve their goals in line with their determined goals. The qualitative aspects of transparency, fair management, formalization and professionalism, which are sub-dimensions of institutionalization in women's cooperatives, and the standardization processes in these cooperatives will be examined. The qualitative aspects of transparency, fair management, formalization and professionalism, which are sub-dimensions of institutionalization in women's cooperatives, and the standardization processes in these cooperatives will be examined. According to the 2020 data of the Ministry of Commerce in Turkey, there are 564 active women's cooperatives in our country. The majority of these are women's enterprise production and business cooperatives. In Bursa, the number of women's cooperatives is 35. It has been observed that the number of women's cooperatives operating in rural areas is 25 and women's cooperatives are predominantly operating in rural areas. The data of this research were collected through in-depth interviews with 21 women consisting of the heads, members of the board of directors and partners of 12 different women's cooperatives operating in Bursa. According to the findings of the research conducted with the qualitative method, 19 of the 21 female members interviewed are married and 2 are single. 9 of these women are between the ages of 20-40, 5 of them are between the ages of 41-50, and 7 of them are 51 years old and over. Among the interviewed participants, 11 people have less than 5 years of experience, while 10 people have more than 5 years of cooperative experience. The fact that the experience of the participants in cooperatives and their working time in their own cooperative is the same shows that they provide continuity in the cooperative they are in. Looking at the age ranges, it can be said that women who have raised their children mostly prefer to be in the management bodies of the cooperative. The leadership style seen in women's co-operatives was seen as autocratic leadership, transformational leadership, liberating leadership, democratic leadership and transactional leadership, respectively. As a result of these interviews, when the prominent findings in the institutionalization of women's cooperatives are examined, it is seen that the level of institutionalization is higher in transformational leadership, autocratic leadership takes the second place, and the lowest institutionalization is under the management of liberal leaders.
Leadership and institutionalization in rural women's cooperatives (Bursa example)
Lisansüstü Eğitim Enstitüsü, Uluslararası Ekonomi Politikası Ana Bilim Dalı, Uluslararası Ekonomi Politikası Bilim Dalı
Keywords: Sosyoloji; Sociology; İşletme